Surface characterization techniques : from theory to research - Kumar, Rawesh (Berlin : De Gruyter, 2022)
This book covers 10 surface characterization techniques divided into three sections. The first section covers the theoretical background, instrumentation and their salient features and a general understanding behind the results. The second section delves into deeper discussion of every terminology and concept. The third section is composed of 5 sets of examples from different research papers for every technique.
Includes bibliographical references, annexures and index.
Keywords: Surfaces (Technology); Surfaces (Technologie); Surfaces (Technology)